Electoral Systems in Albania as a Result of Political Wills - Ã‡eka, Blendi (Richtmann Publishing, 2012)
It is important to note that there is no perfect electoral system model and any country that has to select a new systemis facing a very difficult choice. Of course that is easy to predict the mechanical effects of the chosen system, but when it comesto the psychological effects, the matter is more complicated, because of the institutional, political, cultural and social implications.The choice of electoral system in order to produce positive effects for the political system and society itself must fit maximallywith the context in which it is applied. Questions such as: what is the experience with democracy and democratic institutions,what can be classified as country level of heterogeneity, what is citizen participation in elections, how important is to improve thegender balance, how important is political stability, seem to guide us in determining the most appropriate electoral system for acountry. What is important to note, is that there is no electoral system that guarantees all the dimensions above, so the choiceshould reflect a compromise and fundamental interests of society.